2013
DOI: 10.3402/polar.v32i0.19261
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mapping of plant communities at Hennequin Point, King George Island, Antarctica

Abstract: King George Island is the largest island and the principal area used for research bases in Antarctica. Argentina, Brazil, Chile, China, Poland, Russia, South Korea and Uruguay have permanent open bases on this island. Other countries have seasonal summer stations on different parts of this island, which demonstrates that human impact is strong on King George Island relative to other areas in the maritime and continental Antarctica. The objective of this work was to present a phytosociological approach for ice-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 9 publications
1
24
0
3
Order By: Relevance
“…It is reported from maritime Antarctica (Victoria et al 2013) as well as from continental Antarctica (e.g. Novis et Smissen 2006).…”
Section: Introductionmentioning
confidence: 98%
“…It is reported from maritime Antarctica (Victoria et al 2013) as well as from continental Antarctica (e.g. Novis et Smissen 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Regarding the ecological relationships of D. antarctica, Smykla et al (2007) pointed out that, although it is widely distributed in maritime Antarctica landscapes, it shows a preference for old rookeries and their vicinities, gradually reducing its frequency away from these rich nutrient spots. Victoria et al (2013) found that grasses and mosses in shallow soil developed on the surface of basalt dyke, strongly influenced by L. dominicanus colonies. Overall, mixed plant communities are preferably associated with ornithogenic sites (Simas et al, 2008), and are probably dependent on high nutrient status, as observed in P13, P16 and P12.…”
Section: Moss Turf and Grass Sub-formationmentioning
confidence: 99%
“…The most important sites are coastal penguin rookeries, which provide suitable conditions for plant diversity in their marginal areas (Allen et al, 1967;Tatur and Myrcha, 1989;Tatur et al, 1997;Michel et al, 2006;Smykla et al, 2007;Simas et al, 2007;Victoria et al, 2013). As one moves inland, the vegetation becomes progressively sparse and less structured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant communities formed by Deschampsia Antarctica and Colobanthus quitensis and mixed lichen and mosses are very common in areas close to bird nests (Victoria et al, 2013). They are always associated with increasing SOC (Figure 4).…”
Section: Several Factors May Be Influencing the Ionic Concentration Amentioning
confidence: 99%